Medical Council of Canada Qualifying Examinations and performance in future practice - Wenghofer, Elizabeth; Boulet, John (Canadian Medical Education Journal, 2022)
The purpose of medical licensing examinations is to protect the public from practitioners who do not have adequate knowledge, skills, and abilities to provide acceptable patient care, and therefore evaluating the validity of these examinations is a matter of accountability. Our objective was to discuss the Medical Council of Canada's Qualifying Examinations (MCCQEs) Part I (QE1) and Part II (QE2) in terms of how well they reflect future performance in practice. We examined the supposition that satisfactory performance on the MCCQEs are important determinants of practice performance and, ultimately, patient outcomes. We examined the literature before the implementation of the QE2 (pre-1992), post QE2 but prior to the implementation of the new Blueprint (1992-2018), and post Blueprint (2018-present). The literature suggests that MCCQE performance is predictive of future physician behaviours, that the relationship between examination performance and outcomes did not attenuate with practice experience, and that associations between examination performance and outcomes made sense clinically. While the evidence suggests the MCC qualifying examinations measure the intended constructs and are predictive of future performance, the validity argument is never complete. As new competency requirements emerge, we will need to develop valid and reliable mechanisms for determining practice readiness in these areas.